Guidance on Identifying the Root Causes of Problems In the Coconut Processing Business at the Coconut Processing Centre In Pemenang Subdistrict - Prayitno Basuki; Handry Sudiartha Athar; Baiq Ismiwati; Rahman Dayani (Unram Journal of Community Service, 2026)
The enormous potential of coconuts in North Lombok Regency has encouraged many parties to take an interest in the coconut industry. Unfortunately, the majority of coconut production is sold off-island in the form of whole coconuts, meaning that the economic impact on the development of North Lombok’s economy remains sub-optimal. The presence of coconut processors in Pemenang Sub-district is seen as capable of generating added value, albeit on a relatively small scale. This is due to the numerous business challenges still faced by these coconut processors. This reality has led to uncertainty amongst the artisans regarding which aspect to address first in order to overcome the problems they are currently facing. For this reason, this problem-tree mapping support activity was carried out to guide the artisans in identifying the root causes of the problems. The support began with observation and interviews with key coconut processors, followed by a focus group discussion (FGD) at the coconut processing centre in Pemenang. Previously, the artisans were unable to determine which problems needed to be addressed immediately; however, through this initiative, they have begun to realise that not all problems need to be resolved—it is sufficient to tackle those that constitute the root causes. It is hoped that this mentoring process will serve as a starting point for ongoing capacity-building in the development of coconut processing in Pemenang Sub-district.